Muka Positif dan Muka Negatif pada Majas dalam Puisi “Al-Barda’ah”: Kajian Stilistika dan Pragmatik - Nabila Nur Khonsa; Laily Fitriani; Nur Hasaniyah (Universitas Muhammadiyah Surakarta, 2026)
This research aims to analyze the integration between linguistic aesthetics and politeness strategies by mapping the stanzas of Abdul Hamid Al-Omari's poem, Al-Barda’ah, based on the theories of majas (stylistics) and positive-negative face (pragmatics). Utilizing a qualitative approach, this study demonstrates that face-saving and face-threatening acts can be practically identified through the typological characteristics of the literary devices employed by the author. The analysis of 9 data points reveals that the orientation toward maintaining a positive face (1 datum in the aspect of attention with a caring function) is subtly manifested through Euphemism to reduce confrontational tendencies. Conversely, the preservation of a negative face (8 data points spanning aspects of freedom, not wanting to be disturbed, wanting to be respected, and anger) is realized progressively through variations of Metaphor, Symbolism, Cynicism, and Sarcasm. Through these integrative matrix findings, this study concludes that the choice of majas within the poetic structure is not merely an aesthetic embellishment, but rather the author's pragmatic instrument to assert social positioning, regulate social distance, and maintain self-esteem before the interlocutor.